Contemporary fatwas of Muslim jurists on BBA products : a comparative study between theory and practice - Mohamed, Abdi Fatah Sheikh (Institute of Islamic Banking and Finance, International Islamic University Malaysia, 2010)
Among the popular Islamic banking and financing products is BaiÑ Bithaman Ajil (BBA) which is being widely employed in today's banking institutions. Muslim economists and jurists categorically define BBA as a type of sale where the buyer can pay installment on a differed basis, which includes profit margin agreed on by both the customer and the bank. Because it offers various flexible schemes that are compatible with SharÊÑah rulings, BBA has increasingly become the most dominant product offered by Islamic banks and financing institutions. However, today BBA financial schemes are facing some crucial theoretical and practical challenges. Because of the similarity between some of the BBA financing schemes and conventional interest based financing practices, Justice Abdul Wahab Patail of the High Court of Malaysia ruled that the application of the BBA is contrary to the Islamic Banking Act 1983 taking note that the sale element in BBA “is not bona fide sale”, bringing into question the profit portion of the facility. This and many other questions which concern procedural elements of BBA, particularly about the execution of PPA (Property Purchase Agreement) and PSA (Property Sale Agreement), shows that there is a missing link between theory and practice of BBA schemes thus challenging the financial applications of BBA in contemporary banks which offer Islamic banking products and services. Through comparative and analytical methods, this paper attempts to evaluate the structure, validity and the procedural relevance of BBA financing schemes. Analysis will be extended to the FatwÉs/guidelines issued by AAOIFI, SAC and IFA to find out if there is any possibility of mismatch between BBA FatwÉs and practice. Finally, the paper will provide some suggestions on how to overcome the contemporary challenges faced by BBA and improve its schemes.